Development of Family Welfare Values in Community Civic by Way of Sekoper Cinta Program - Agung Rusmana; Suwarma Al Muchtar; Syaifullah Syaifullah (Jurnal Civicus, 2021)
This research was conducted to look at the implementation, achievements, constraints, and efforts of the West Java’s Government Program, it’s called Sekolah Perempuan Capai Impian dan Cita-cita (Sekoper Cinta) to developing family welfare values in Community Civic. This topic based on curiosity about West Java Government Policies in overcoming family problems by promoting women as agents of family welfare development in West Java. Sekoper Cinta is a non-formal education program that collaborates with the concept of Community Civic. This research was conducted using a qualitative approach. Data and information was collected through interviews, observation, and documentation study. This study was conducted in Galanggang Village, Batujajar District, West Bandung Regency as a pilot project location of this program. The conclusion in this study describes the urgency of developing family welfare in the Sekoper Cinta program through Community Civic, then the achievements and methods used in the process of internalizing the values of family welfare